2019
DOI: 10.1021/acscatal.8b05162
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Ceria-Supported Ru Catalyst for the Dry Reforming of Methane: In Situ Identification of Ruδ+–Ce3+ Interactions for Enhanced Conversion

Abstract: The metal−oxide interaction changes the surface electronic states of catalysts deployed for chemical conversion, yet details of its influence on the catalytic performance under reaction conditions remain obscure. In this work, we report the high activity/stability of a ceria-supported Ru−nanocluster (<1 nm) catalyst during the dry reforming of methane. To elucidate the structure−reactivity relationship underlying the remarkable catalytic performance, the active structure and chemical speciation of the catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(112 citation statements)
references
References 57 publications
4
104
0
4
Order By: Relevance
“…Very recently, Liu and co-workers proposed another ceria-based catalyst formulation for dry reforming of methane by changing the nature of the supported metal, a key component in such catalytic process [149]. In their work, they reported a highly active and stable ceria-supported Ru-nanocluster (< 1 nm) catalyst (denoted as Ru(NC)−CeO 2 ) for the DRM, since Ru-based catalysts have exhibited high activity and stability against the deactivation by carbon accumulation [257,263].…”
Section: Dry Reforming Of Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Liu and co-workers proposed another ceria-based catalyst formulation for dry reforming of methane by changing the nature of the supported metal, a key component in such catalytic process [149]. In their work, they reported a highly active and stable ceria-supported Ru-nanocluster (< 1 nm) catalyst (denoted as Ru(NC)−CeO 2 ) for the DRM, since Ru-based catalysts have exhibited high activity and stability against the deactivation by carbon accumulation [257,263].…”
Section: Dry Reforming Of Hydrocarbonsmentioning
confidence: 99%
“…(a) Ce 3d and (b) C 1s + Ru 3d NAP-XPS spectra of the 0.5 wt % Ru(NC)-CeO 2 catalyst under~0.13 mbar CH 4 /CO 2 (1:1). Reprinted with permission from[149], copyright 2019, American Chemical Society.…”
mentioning
confidence: 99%
“…Bands at ≈2130 cm −1 were assigned to Ru‐multicarbonyl species adsorbed at undercoordinated Ru atoms, e.g., at the periphery interface sites of the Ru NPs, with more than one CO adsorbed on low‐coordination Ru atoms [21, 26, 27] . In a recent study, bands ≈2070–2080 cm −1 were assigned to asymmetric stretch vibrations of the above species and to CO on‐top adsorbed on Ru sites that are electronically modified by interaction with the substrate (“monolayer sites”), [21] e.g., sites at the interface perimeter [16, 28] . Bands in the range 2000–2050 cm −1 were associated with on‐top CO adsorbed on Ru NPs, [21, 26, 27] while bands below that range were attributed with bridge‐bonded CO [28] …”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated recently that the activity of Ru/TiO 2 catalysts for CO 2 methanation could be significantly improved by ahigh temperature reaction treatment in reductive atmosphere,which we had attributed to amodification of the metal-support interactions (MSIs), [10] for example,b ys tabilization of metal NPs and/or charge transfer effects. [6,11,12] Va riation in the catalytic performance due to modification of MSIs has been considered for decades for noble metal catalysts supported on reducible oxides under reductive reaction conditions, [13][14][15][16] including also CO 2 hydrogenation, [10,17,18] but not for stable (inert) oxides such as Al 2 O 3 . [6] Recent experimental and theoretical studies,h owever, indicated as tabilization of noble metals on penta-coordinated Al 3+ sites,r eflecting am odification of the MSIs that could lead also to the formation of flat NPs.…”
Section: Introductionmentioning
confidence: 99%
“…auf den Atomen am Übergang zum Oxid [21, 26, 27] . In einer neueren Arbeit wurde die Komponente bei ≈2070–2080 cm −1 der asymmetrischen Streckschwingung dieser Multicarbonyl Spezies zugeordnet, aber auch CO ad , dass “on‐top” auf Ru Atomen adsorbiert ist, die durch Wechselwirkung mit dem Träger elektronisch modifiziert sind (“Monolagen‐Plätze”), [21] oder Grenzflächenplätzen bei hemisphärischen Partikeln [16, 28] . Signale im Bereich 2000–2050 cm −1 und im Bereich darunter wurden schließlich CO ad zugeordnet, das entweder on‐top oder auf Brückenplätzen auf den Ru NPs adsorbiert ist [21, 26–28] …”
Section: Ergebnisse Und Diskussionunclassified